IsiXhosa storytelling (iintsomi) as an alternative medium for maternal health education in primary healthcare in the Eastern Cape - Zakaza, Nompucuko (Rhodes University, Faculty of Humanities, School of Languages, 2015)
The aim of this study is to explore the introduction of IsiXhosa (iintsomi) as an alternative method in the maternal health education in rural Primary Health Care in the Eastern Cape. An informal preliminary observation of a maternal health lesson by the researcher indicated a further need for maternal health educators to introduce storytelling into the health content themes. To re-inforce the maternal health educator lesson on the causes of teenage pregnancy, lifestyles for pregnant women, causes of miscarriage and termination of pregnancy, the Community Health Workers can undoubtedly use isiXhosa iintsomi in selected clinics and maternal waiting homes. As a readily available resource that cuts across all literacy barriers, iintsomi (isiXhosa) fosters a cross-cultural consultation which enables the healthcare worker to convey messages that make sense to the rural women. While the conventional methods of teaching have a tendency to create tension and lack of participation, use of folktale (iintsomi) have huge potential to bring lesson enjoyment; a meaningful interaction and story sharing by the maternal health educator, the pregnant women and greater community; access to important health messages; and strengthened utilisation of Primary Health Care. The study therefore suggests that there is a place for isiXhosa iintsomi: From the Fireplace into the Workplace.
Keywords: Communication in community health services -- South Africa -- Eastern Cape; Communication in reproductive health -- South Africa -- Eastern Cape; Storytelling in education; Applied folklore